2006
DOI: 10.1073/pnas.0506997103
|View full text |Cite
|
Sign up to set email alerts
|

Optophysiology: Depth-resolved probing of retinal physiology with functional ultrahigh-resolution optical coherence tomography

Abstract: Noncontact, depth-resolved, optical probing of retinal response to visual stimulation with a <10-m spatial resolution, achieved by using functional ultrahigh-resolution optical coherence tomography (fUHROCT), is demonstrated in isolated rabbit retinas. The method takes advantage of the fact that physiological changes in dark-adapted retinas caused by light stimulation can result in local variation of the tissue reflectivity. fUHROCT scans were acquired from isolated retinas synchronously with electrical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(147 citation statements)
references
References 34 publications
4
142
0
1
Order By: Relevance
“…Moreover, measuring the reflectance of the various retinal layers on OCT images may also be of interest. Drexler et al have shown in in vitro and in vivo (Bizheva et al, 2006;Hermann et al, 2006) studies that physiological processes of the retina lead to optical density changes that can be observed by a special M-mode OCT imaging, known as optophysiology. Thus, it also seems rational that quantitative analysis of reflectance changes may provide clinically relevant information in retinal patophysiology.…”
Section: Quantitative Measurements Of Retinal Morphologymentioning
confidence: 99%
“…Moreover, measuring the reflectance of the various retinal layers on OCT images may also be of interest. Drexler et al have shown in in vitro and in vivo (Bizheva et al, 2006;Hermann et al, 2006) studies that physiological processes of the retina lead to optical density changes that can be observed by a special M-mode OCT imaging, known as optophysiology. Thus, it also seems rational that quantitative analysis of reflectance changes may provide clinically relevant information in retinal patophysiology.…”
Section: Quantitative Measurements Of Retinal Morphologymentioning
confidence: 99%
“…It is also the key to imaging large comprehensive 3 D volumes [173] or to the time-resolved observation of dynamic processes [44,45,167]. The recent commercialization of high speed line cameras and swept sources will therefore be an important factor driving the development of the next generation of OCT systems.…”
Section: Developments In Ophthalmic Octmentioning
confidence: 99%
“…Compared to other techniques like electro-retinography, OCT provides uncomplicated, non-invasive access for studying the retinal physiology, and may open new possibilities to investigate retinal pathologies [44,167].…”
Section: Developments In Ophthalmic Octmentioning
confidence: 99%
See 1 more Smart Citation
“…In a healthy macula, IS/OS junction can be seen as a continuous hyper-reflective band on OCT image, and recent studies demonstrated that decreased reflectivity of this layer is associated with diminished photoreceptor function. 18,19 Based on this knowledge, loss of reflectivity in IS/OS junction and ELM might indicate that EMM leads to subclinical functional or structural impairment in these layers. However, correlation analysis did not show a significant association between reflectivity values and CDVA.…”
Section: Is/os Reflectivity In Epimacular Membrane I Toprak Et Almentioning
confidence: 99%